RECONSTRUCTION OF ARC STEEL-MELTING FURNACE TO INCREASE PRODUCTIVITY AT JSC «BSW MANAGEMENT COMPANY OF HOLDING «ВМС» - V. Yu. Girilovich (Литьë и металлургия, 2015)
Article is devoted to consideration of questions of increasing productivities of arc steel-melting furnace No. 1 (ESMS-1) and at the same time to reduction of a consumption of energy resources. In article the choice of reconstructive actions is considered on the analysis of complex of elements of technology of the highest level when melting steel in arc steel-melting furnace. The main actions of reconstruction and the introduced technologies are described and considered.